A back contact cell and a method of manufacturing the same

CN122909934APending Publication Date: 2026-10-13宜宾英发德耀科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611099290.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-23
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

然而,用铝金属代替银金属,以及贱金属工艺面临接触差、贱金属扩散带来的金属复合加剧等问题,进而影响电池效率

Benefits of technology

本发明用铝金属以及贱金属代替银金属作为电池的金属电极,通过设置扩散阻挡层内的金属-硅固相过渡层与第二隧穿氧化层的距离为1-10nm,从而阻挡高温下的铝向隧穿氧化层中扩散,避免铝刺破隧穿氧化层;适当的距离,也避免了由于距离过大导致电阻过大。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122909934A_ABST
    Figure CN122909934A_ABST
Patent Text Reader

Abstract

The application discloses a back contact cell and a preparation method thereof, and relates to the technical field of photovoltaic cells. In the application, aluminum metal and base metal are used to replace silver metal as the metal electrode of the cell, and the distance between the metal-silicon solid phase transition layer in the diffusion barrier layer and the second tunneling oxide layer is 1-10 nm, so that the diffusion of aluminum into the tunneling oxide layer under high temperature is blocked, and the tunneling oxide layer is prevented from being punctured by aluminum. The back contact cell provided by the application has low preparation cost, and the cell efficiency is on a par with that of the silver metal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of photovoltaic cell technology, and more specifically, to a back contact cell and its preparation method. Background Technology

[0002] Currently, with rising silver prices, the manufacturing cost of photovoltaic cells continues to increase. Silver paste cost has become a key factor restricting the industry's development, necessitating the search for alternatives. Current alternatives include silver-coated copper, copper, nickel, and aluminum. However, using aluminum instead of silver, and the challenges of base metal processes such as poor contact and increased metal recombination due to base metal diffusion, all negatively impact cell efficiency.

[0003] In view of this, the present invention is proposed. Summary of the Invention

[0004] The purpose of this invention is to provide a back contact battery and its preparation method to solve the above-mentioned technical problems.

[0005] This invention is implemented as follows: In a first aspect, the present invention provides a back contact battery, comprising: a substrate having a backlight surface and a light-facing surface disposed opposite to each other, the backlight surface having a first polarity region and a second polarity region; the first polarity region and the second polarity region having different polarities; Both the first polar region and the second polar region are provided with at least three tunneling oxide layers. When there are three tunneling oxide layers, both the first polar region and the second polar region are provided with a first tunneling oxide layer, a doped polysilicon layer, a second tunneling oxide layer, a diffusion barrier layer, a third tunneling oxide layer and an anti-reflection layer along the thickness direction away from the substrate. Both the first polar region and the second polar region have metal electrode regions. Along the thickness direction away from the substrate, the metal electrode regions are provided with a metal-silicon solid phase transition layer and metal electrodes. The metal electrodes are selected from one or more of copper, aluminum, nickel and tin. The metal-silicon solid-phase transition layer is located within the diffusion barrier layer or simultaneously within the diffusion barrier layer and the doped polycrystalline silicon layer. When the metal-silicon solid phase transition layer is located within the diffusion barrier layer, the distance between the end of the metal-silicon solid phase transition layer away from the metal electrode and the second tunneling oxide layer is 1-10 nm. When the metal-silicon solid-phase transition layer is located in both the diffusion barrier layer and the doped polycrystalline silicon layer, the distance between the end of the metal-silicon solid-phase transition layer away from the metal electrode and the first tunneling oxide layer is 10-150 nm. There is an isolation zone between the first polarity region and the second polarity region.

[0006] Secondly, the present invention also provides a method for preparing a back contact battery, which includes the following steps: S1: Prepare a second tunneling oxide layer, a diffusion barrier layer, and a third tunneling oxide layer on the back side of the substrate after removing the wrap-around plating. S2: An antireflection layer is prepared on the back side of the substrate; S3: Print metal paste in the metal electrode regions of the first polarity region and the second polarity region; S4: Sintering. When the printed metal paste is silver paste, the sintering temperature is 500~577℃ and the time is 1~60min; when the printed metal paste is copper paste, the sintering temperature is 800~900℃ and the time is 1~60min; when the printed metal paste is nickel paste, the sintering temperature is 900~1150℃ and the time is 1~60min; when the printed metal paste is tin paste, the sintering temperature is 200~300℃ and the time is 1~60min.

[0007] The present invention has the following beneficial effects: This invention uses aluminum and base metals instead of silver as the metal electrodes of the battery. By setting the distance between the metal-silicon solid phase transition layer and the second tunneling oxide layer in the diffusion barrier layer to 1-10 nm, aluminum at high temperature is prevented from diffusing into the tunneling oxide layer, thus avoiding aluminum from piercing the tunneling oxide layer. The appropriate distance also avoids excessive resistance due to excessive distance.

[0008] When the metal-silicon solid-phase transition layer is located within both the diffusion barrier layer and the doped polycrystalline silicon layer, the distance between the end of the metal-silicon solid-phase transition layer furthest from the metal electrode and the first tunneling oxide layer is 10-150 nm. This distance can prevent aluminum at high temperatures from diffusing into the first tunneling oxide layer, and an appropriate distance also avoids excessive resistance due to excessive distance.

[0009] This invention also provides a method for fabricating a back-contact battery, which limits the sintering temperature of the printed aluminum paste to 500-577℃ and the time to 1-60 min. When the sintering temperature exceeds 577℃, aluminum undergoes a liquid-phase eutectic reaction in silicon. This invention strictly limits the sintering temperature to 500-577℃, ensuring that aluminum and silicon only contact in solid form, resulting in only solid-phase diffusion. This reduces the migration of aluminum metal in silicon, lowering its migration rate and depth. It avoids excessively high sintering temperatures, which could lead to the formation of a eutectic liquid phase between aluminum and silicon. This liquid phase has extremely high fluidity and would rapidly dissolve and erode the silicon substrate, forming sharp "aluminum spikes," leading to a decrease in battery efficiency.

[0010] The back-contact battery provided by this invention has low manufacturing cost and battery efficiency comparable to that of silver. Attached Figure Description

[0011] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0012] Figure 1 This is a schematic diagram of the structure of the back contact battery provided by the present invention; Figure 2 This is an enlarged schematic diagram of the metal electrode region; Figure 3 This is a schematic diagram of the back contact battery provided in Embodiment 4 of the present invention; Figure 4 This is an enlarged schematic diagram of the metal electrode region in Example 4.

[0013] Reference numerals: 1-N-type crystalline silicon; 2-First tunneling oxide layer; 3-Intrinsic polycrystalline silicon; 4-Second tunneling oxide layer; 5-Antireflection layer; 6-P-type polycrystalline silicon; 7-N-type polycrystalline silicon; 8-Metal-silicon solid-phase transition layer; 9-Silicon oxide; 10-Metal oxide layer; 11-Metal electrode; 12-Third tunneling oxide layer; 13-Isolation region; 14-Metal electrode region. Detailed Implementation

[0014] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0015] The inventors discovered that base metals, such as aluminum, diffuse into silicon at high temperatures, causing metal recombination and affecting battery efficiency. Specifically, according to the aluminum-silicon binary phase diagram, when the temperature reaches 577°C, aluminum and silicon form a eutectic liquid phase. This liquid phase is extremely fluid, rapidly dissolving and eroding the silicon substrate, forming sharp "aluminum spikes." When the temperature is below 577°C, aluminum and silicon only contact in solid form, and aluminum atoms need to overcome a high energy barrier to diffuse through point defects such as vacancies or grain boundaries in the silicon lattice. Compared to the liquid-phase eutectic, solid-phase diffusion is slower and has a shallower migration depth. This invention strictly limits the sintering temperature to below 577°C, ensuring that aluminum and silicon only contact in solid form, resulting in only solid-phase diffusion and reducing aluminum migration within silicon.

[0016] In a first aspect, the present invention provides a back contact battery, comprising: a substrate having a backlight surface and a light-facing surface disposed opposite to each other, the backlight surface having a first polarity region and a second polarity region; the first polarity region and the second polarity region having different polarities; Both the first polar region and the second polar region are provided with at least three tunneling oxide layers. When there are three tunneling oxide layers, the first polar region and the second polar region are provided with a first tunneling oxide layer 2, a doped polysilicon layer, a second tunneling oxide layer 4, a diffusion barrier layer, a third tunneling oxide layer 12 and an anti-reflection layer 5 along the thickness direction away from the substrate. Both the first polar region and the second polar region have a metal electrode region 14. The metal electrode region 14 is provided with a metal-silicon solid phase transition layer 8 and a metal electrode 11 along the thickness direction away from the substrate. The metal electrode 11 is selected from one or more of copper, aluminum, nickel and tin. Among them, the metal-silicon solid phase transition layer 8 is located within the diffusion barrier layer or simultaneously within the diffusion barrier layer and the doped polycrystalline silicon layer; When the metal-silicon solid transition layer 8 is located within the diffusion barrier layer, the distance between the end of the metal-silicon solid transition layer 8 away from the metal electrode 11 and the second tunneling oxide layer 4 is 1-10 nm. When the metal-silicon solid transition layer 8 is located in both the diffusion barrier layer and the doped polycrystalline silicon layer, the distance between the end of the metal-silicon solid transition layer 8 away from the metal electrode 11 and the first tunneling oxide layer 2 is 10-150 nm. There is an isolation zone 13 between the first polar region and the second polar region.

[0017] To reduce production costs, aluminum and base metals are used instead of silver as the metal electrode 11 of the battery. By setting the distance between the metal-silicon solid phase transition layer 8 in the diffusion barrier layer and the second tunneling oxide layer 4 to 1-10 nm, aluminum at high temperature is prevented from diffusing into the tunneling oxide layer, thus avoiding aluminum from piercing the tunneling oxide layer. The appropriate distance also avoids excessive resistance due to excessive distance.

[0018] In another embodiment, when the metal-silicon solid-phase transition layer 8 is located within both the diffusion barrier layer and the doped polycrystalline silicon layer, the distance between the end of the metal-silicon solid-phase transition layer 8 away from the metal electrode 11 and the first tunneling oxide layer 2 is 10-150 nm. This distance can prevent aluminum at high temperatures from diffusing into the first tunneling oxide layer 2, and an appropriate distance also avoids excessive resistance due to excessive distance.

[0019] The back contact battery with the above structure uses aluminum and base metals to prepare the metal electrode 11, which has low preparation cost and battery efficiency comparable to that of silver.

[0020] In a preferred embodiment of the present invention, the diffusion barrier layer is selected from intrinsic polycrystalline silicon 3, titanium nitride, silicide, or nickel-aluminum alloy.

[0021] Any method that can prevent aluminum from diffusing at high temperatures, provide a certain degree of insulation, and maintain an appropriate distance between the metal-silicon solid phase transition layer 8 and the tunneling oxide layer is feasible.

[0022] If the distance between the metal-silicon solid phase transition layer 8 and the tunneling oxide layer is too large, the resistance will increase; if it is too small, there is a risk that aluminum will puncture the tunneling oxide layer.

[0023] In a preferred embodiment of the present invention, when the metal-silicon solid-phase transition layer 8 is located within the diffusion barrier layer, the distance between the end of the metal-silicon solid-phase transition layer 8 away from the metal electrode 11 and the second tunneling oxide layer 4 is 4-10 nm; at this distance, the diffusion barrier layer can have both good insulation effect and the effect of blocking aluminum amplification at high temperature.

[0024] In a preferred embodiment of the present invention, the distance between the end of the metal-silicon solid-phase transition layer 8 away from the metal electrode 11 and the second tunneling oxide layer 4 is 4-8 nm.

[0025] When the tunneling oxide layer is N layers and N is greater than 3, the first polar region and the second polar region are both provided with a first tunneling oxide layer 2, a multilayer stacked layer of doped polysilicon layer and tunneling oxide layer, a diffusion barrier layer, an N-1th tunneling oxide layer and an antireflection layer 5 along the thickness direction away from the substrate; the multilayer stacked layer includes multiple repeating units, and each repeating unit includes a doped polysilicon layer and a tunneling oxide layer arranged sequentially.

[0026] For example, when both the first polar region and the second polar region are provided with four tunneling oxide layers, the first polar region and the second polar region are provided with the first tunneling oxide layer 2, the first doped polysilicon layer, the second tunneling oxide layer 4, the second doped polysilicon layer, the third tunneling oxide layer 12, the diffusion barrier layer, the fourth tunneling oxide layer and the antireflection layer 5 in sequence along the thickness direction away from the substrate.

[0027] In a preferred embodiment of the present invention, the thickness of any tunneling oxide layer is 0.5~2 nm, the thickness of the doped polysilicon layer is 10~150 nm, the thickness of the diffusion barrier layer is 5~50 nm, and the thickness of the antireflection layer 5 is 50~100 nm. The 10-150 nm thickness of the doped polysilicon layer increases the process window for aluminum diffusion, while the 5-50 nm thickness of the diffusion barrier layer ensures effective blocking while also allowing carriers to tunnel through.

[0028] The thickness of any tunneling oxide layer is, for example, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 or 2.0 nm.

[0029] The thickness of the doped polycrystalline silicon layer is 10-20nm, 10-50nm, 30-60nm, 50-80nm, 60-100nm, 60-130nm or 110-150nm.

[0030] The thickness of the diffusion barrier layer is 5-10nm, 5-20nm, 8-30nm, 8-40nm or 10-50nm.

[0031] The thickness of the antireflection layer 5 is 50-60nm, 50-70nm, or 60-100nm.

[0032] In a preferred embodiment of the present invention, the metal electrode region 14 is provided with a metal-silicon solid phase transition layer 8, silicon oxide 9, a metal oxide layer 10 and a metal electrode 11 along the thickness direction away from the substrate.

[0033] In a preferred embodiment of the present invention, the thickness of the metal-silicon solid-phase transition layer 8 is 10~150nm, the thickness of the silicon oxide 9 is 0~2nm, the thickness of the metal oxide layer 10 is 0~2nm, and the thickness of the metal electrode 11 is 1~20μm.

[0034] The thickness of the metal-silicon solid-phase transition layer 8 is 10-20 nm, 10-50 nm, 30-60 nm, 50-80 nm, 60-100 nm, 60-130 nm, or 110-150 nm; the thickness of the silicon oxide 9 is 0, 0.1, 0.2, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, or 2.0 nm; the thickness of the metal oxide layer 10 is 0, 0.1, 0.2, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, or 2.0 nm; and the thickness of the metal electrode 11 is 1-5 μm. 5-10μm or 5-20μm.

[0035] In a preferred embodiment of the present invention, the isolation region 13 is provided with a first tunneling oxide layer 2, a diffusion barrier layer, a second tunneling oxide layer 4, and an anti-reflection layer 5 along the thickness direction away from the substrate.

[0036] Secondly, the present invention also provides a method for preparing a back contact battery, which includes the following steps: S1: Prepare a second tunneling oxide layer 4, a diffusion barrier layer, and a third tunneling oxide layer 12 on the back side of the substrate after removing the wrap-around plating. S2: An antireflection layer 5 is prepared on the back side of the substrate; S3: Print metal paste in the metal electrode region 14 of the first polarity region and the second polarity region; S4: Sintering. When the printed metal paste is silver paste, the sintering temperature is 500~577℃ and the time is 1~60min; when the printed metal paste is copper paste, the sintering temperature is 800~900℃ and the time is 1~60min; when the printed metal paste is nickel paste, the sintering temperature is 900~1150℃ and the time is 1~60min; when the printed metal paste is tin paste, the sintering temperature is 200~300℃ and the time is 1~60min.

[0037] Excessively high sintering temperatures and excessively long sintering times can cause aluminum and base metals to puncture the tunnel oxide layer, leading to passivation failure of the tunnel oxide layer.

[0038] Base metals are selected from metals such as copper, iron, aluminum, lead, tin, zinc, and nickel.

[0039] When the printed metal paste is selected from silver paste, the sintering temperature is, for example, 500-520℃, 520-550℃, 530-560℃, 540-570℃, 555-575℃, or 560-577℃. The sintering time is 1-30min, 5-10min, 10-40min, 15-50min, or 15-60min.

[0040] In a preferred embodiment of the present invention, when the printed metal paste is selected from silver paste, the sintering temperature is 500~577℃ and the time is 1~30min.

[0041] In a preferred embodiment of the present invention, when the printed metal paste is selected from silver paste, the sintering temperature is 500~577℃ and the time is 5~30min. Under these sintering conditions, it can be ensured that aluminum and base metals maintain solid-phase diffusion.

[0042] The features and performance of the present invention will be further described in detail below with reference to embodiments.

[0043] Example 1 This embodiment provides a method for preparing a back contact battery, which includes the following steps: S1: N-type crystalline silicon 1 undergoes double-sided polishing; S2: An oxide layer and intrinsic polysilicon 3 are deposited on the back side using LPCVD. The thickness of the tunneling oxide layer is 1.5 nm, and the thickness of the intrinsic polysilicon 3 is 100 nm. S3: Boron diffusion is performed on intrinsic polysilicon 3 at a concentration of 8E19. S4: Laser grooving is performed in a region of doped polycrystalline silicon. The laser is a 355nm purple picosecond laser with a power of 40W. S5: Perform alkaline polishing on the sample after laser grooving; S6: LPCVD deposition of tunneling silicon oxide 9 and intrinsic polysilicon 3 was performed on the polished sample. The thickness of the tunneling silicon oxide 9 layer was 1.5 nm, and the thickness of the intrinsic polysilicon 3 layer was 100 nm. S7: Phosphorus diffusion is performed on intrinsic polysilicon 3 at a concentration of 3E20; S8: Laser grooving is performed on the excess phosphorus-doped polysilicon region in the P-region. The laser is a 532nm green picosecond laser with a power of 40W. S9: Remove the front-side plating and texturing using a wet chemical method to form a textured surface in the isolation area 13 between the front and back sides of the sample. S10: Aluminum oxide (i.e., passivation layer) is deposited on the front side of the sample using ALD, with an aluminum oxide thickness of 5 nm; S11: Silicon nitride antireflection film deposited on the front side, with a thickness of 80nm; S12: Remove the back side bypass using a chain cleaning process; the HF concentration is 15 wt%. S13: A tunneling oxide layer, intrinsic polysilicon 3, and a tunneling oxide layer are deposited on the back side using LPCVD. The thickness of the tunneling oxide layer is 1.5 nm, and the thickness of the intrinsic polysilicon 3 is 30 nm. S14: Remove the tunneling oxide layer, intrinsic polysilicon 3, and tunneling oxide layer from the front-side plating using chain alkaline polishing; S15: Backside deposition of silicon nitride antireflection film, 80nm thick; S16: Aluminum paste is printed on the P and N regions of the back side emitter (i.e., metal electrode 11); S17: Dry and sinter the printed aluminum paste at 560℃ for 40 minutes (the metal-silicon solid phase transition layer 8 and the metal oxide layer 10 are formed during drying and sintering). S18: Test battery efficiency.

[0044] Figure 1 As shown, on the back side of the N-type crystalline silicon, there are P-type regions and N-type regions; there is an isolation region 13 between them.

[0045] The P-type region is provided with a first tunneling oxide layer 2, a P-type polysilicon 6 (i.e., doped polysilicon), a second tunneling oxide layer 4, an intrinsic polysilicon 3, a third tunneling oxide layer 12, and an anti-reflection layer 5 in sequence along the direction away from the substrate thickness. In the N-type region, a first tunneling oxide layer 2, an N-type polysilicon 7 (i.e., doped polysilicon), a second tunneling oxide layer 4, an intrinsic polysilicon 3, a third tunneling oxide layer 12, and an anti-reflection layer 5 are sequentially disposed along the direction away from the substrate thickness. The isolation zone 13 is provided with a first tunneling oxide layer 2, an intrinsic polysilicon layer 3, a second tunneling oxide layer 4, and an antireflection layer 5 in sequence along the direction away from the thickness of the substrate.

[0046] Both the P-type and N-type regions have metal electrode regions 14, and the metal electrode regions 14 are provided with a metal-silicon solid-phase transition layer 8, silicon oxide 9, a metal oxide layer 10 and a metal electrode 11 along the thickness direction away from the substrate. Figure 2 ).

[0047] In this embodiment, the distance between the end of the metal-silicon solid-phase transition layer 8 away from the metal electrode 11 and the second tunneling oxide layer 4 is 10 nm.

[0048] Example 2 Compared with Example 1, the only difference is that in step S13 of this example, the thickness of the intrinsic polycrystalline silicon 3 is 15 nm. The other steps are the same.

[0049] Example 3 Compared with Example 1, the only difference is that in step S17, drying and sintering are performed at a temperature of 540°C for 20 minutes. All other steps are the same.

[0050] Example 4 Compared to Example 1, the only difference is that in Example 1, the metal-silicon solid-phase transition layer 8 is located within the diffusion barrier layer. In this example, the metal-silicon solid-phase transition layer 8 is located simultaneously within both the diffusion barrier layer and the doped polycrystalline silicon layer. The specific fabrication process is as follows: Compared with Example 1, the only difference is in S13: the thickness of the tunnel oxide layer is 1.5 nm, the thickness of the intrinsic polycrystalline silicon 3 is 10 nm, and the rest is the same as in Example 1.

[0051] Structural diagram reference Figure 3 and Figure 4 As shown.

[0052] Example 5 Compared with Example 1, the only difference is in steps S16 and S17.

[0053] S16: Copper paste is printed on the P and N regions on the back (i.e., metal electrode 11); S17: Dry and sinter the printed copper paste at 850°C for 5 minutes (the metal-silicon solid phase transition layer 8 and the metal oxide layer 10 are formed during drying and sintering).

[0054] Example 6 Compared with Example 1, the only difference is in steps S16 and S17.

[0055] S16: Nickel paste is printed on the emitters (i.e., metal electrodes 11) in the P and N regions on the back side; S17: Dry and sinter the printed nickel paste at 970°C for 5 minutes (the metal-silicon solid phase transition layer 8 and the metal oxide layer 10 are formed during drying and sintering).

[0056] Comparative Example 1 Compared with Example 1, the only difference is in step S16: printing silver paste on the emitters (i.e., metal electrodes 11) of the P and N regions on the back side. The sintering temperature is 700°C and the time is 10 seconds.

[0057] Comparative Example 2 Compared with Example 1, the only difference is that the distance between the end of the metal-silicon solid phase transition layer 8 away from the metal electrode 11 and the second tunneling oxide layer 4 is 15 nm.

[0058] Experimental Example 1 The cell efficiency of the back-contact crystalline silicon solar cells prepared in Examples 1-4 and Comparative Examples 1-2 was tested respectively. The testing method was the conventional crystalline silicon solar cell testing method, IV test (test conditions: temperature 25℃, light intensity 1000w / m²): The efficiency of the crystalline silicon back-contact battery produced by this invention is comparable to that of silver.

[0059]

[0060] Experimental results show that using aluminum instead of silver as the electrode can reduce costs; and the battery efficiency is comparable to that of silver electrodes. In Comparative Example 2, the distance between the end of the metal-silicon solid-phase transition layer 8 furthest from the metal electrode 11 and the second tunneling oxide layer 4 exceeds 10 nm, which leads to an increase in battery resistance.

[0061] Intrinsic polycrystalline silicon 3 and Al only undergo solid-phase diffusion below 577℃, and intrinsic polycrystalline silicon 3 has a good blocking effect; metallic aluminum and silicon oxide 9 undergo a displacement reaction at 500~577℃ to generate AlOx, and AlOx can further block the migration of aluminum.

[0062] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A back-contact battery, characterized in that, It includes: substrate The substrate has a backlight surface and a light-facing surface disposed opposite to each other, and the backlight surface is provided with a first polarity region and a second polarity region; The first polarity region and the second polarity region have different polarities; The first polar region and the second polar region are each provided with at least three tunneling oxide layers. When there are three tunneling oxide layers, the first polar region and the second polar region are each provided with a first tunneling oxide layer, a doped polysilicon layer, a second tunneling oxide layer, a diffusion barrier layer, a third tunneling oxide layer and an antireflection layer along the thickness direction away from the substrate. Both the first polar region and the second polar region have metal electrode regions. The metal electrode regions are provided with a metal-silicon solid-phase transition layer and a metal electrode along the thickness direction away from the substrate. The metal electrode is selected from one or more of copper, aluminum, nickel and tin. The metal-silicon solid-phase transition layer is located within the diffusion barrier layer or simultaneously within the diffusion barrier layer and the doped polycrystalline silicon layer. When the metal-silicon solid phase transition layer is located within the diffusion barrier layer, the distance between the end of the metal-silicon solid phase transition layer away from the metal electrode and the second tunneling oxide layer is 1-10 nm; When the metal-silicon solid-phase transition layer is located within both the diffusion barrier layer and the doped polycrystalline silicon layer, the distance between the end of the metal-silicon solid-phase transition layer away from the metal electrode and the first tunneling oxide layer is 10-150 nm. There is an isolation zone between the first polar region and the second polar region.

2. The back contact battery according to claim 1, characterized in that, The diffusion barrier layer is selected from intrinsic polycrystalline silicon, titanium nitride, silicide, or nickel-aluminum alloy.

3. The back contact battery according to claim 2, characterized in that, When the metal-silicon solid phase transition layer is located within the diffusion barrier layer, the distance between the end of the metal-silicon solid phase transition layer away from the metal electrode and the second tunneling oxide layer is 4-10 nm. Preferably, the distance between the end of the metal-silicon solid-phase transition layer away from the metal electrode and the second tunneling oxide layer is 4-8 nm; When the tunneling oxide layer is N layers and N is greater than 3, the first polar region and the second polar region are each provided with a first tunneling oxide layer, a multilayer stacked layer of doped polysilicon layer and tunneling oxide layer, a diffusion barrier layer, an (N-1)th tunneling oxide layer and an antireflection layer along the thickness direction away from the substrate; the multilayer stacked layer includes multiple repeating units, and each repeating unit includes a doped polysilicon layer and a tunneling oxide layer arranged sequentially.

4. The back contact battery according to claim 3, characterized in that, The thickness of any one of the tunneling oxide layers is 0.5~2nm, the thickness of the doped polycrystalline silicon layer is 10~150nm, the thickness of the diffusion barrier layer is 5~50nm, and the thickness of the antireflection layer is 50~100nm.

5. The back contact battery according to claim 2, characterized in that, The metal electrode region is provided with a metal-silicon solid-phase transition layer, silicon oxide, a metal oxide layer and a metal electrode along the thickness direction away from the substrate.

6. The back contact battery according to claim 5, characterized in that, The thickness of the metal-silicon solid-phase transition layer is 10~150nm, the thickness of the silicon oxide is 0~2nm, the thickness of the metal oxide layer is 0~2nm, and the thickness of the metal electrode is 1~20μm.

7. The back contact battery according to claim 2, characterized in that, The isolation region is provided with a first tunneling oxide layer, a diffusion barrier layer, a second tunneling oxide layer, and an anti-reflection layer along the thickness direction away from the substrate.

8. The method for preparing a back contact battery according to any one of claims 1-7, characterized in that, It includes the following steps: S1: Prepare a second tunneling oxide layer, a diffusion barrier layer, and a third tunneling oxide layer on the back side of the substrate after removing the wrap-around plating. S2: An antireflection layer is prepared on the back side of the substrate; S3: Print metal paste in the metal electrode regions of the first polarity region and the second polarity region; S4: Sintering. When the printed metal paste is silver paste, the sintering temperature is 500~577℃ and the time is 1~60min; when the printed metal paste is copper paste, the sintering temperature is 800~900℃ and the time is 1~60min; when the printed metal paste is nickel paste, the sintering temperature is 900~1150℃ and the time is 1~60min; when the printed metal paste is tin paste, the sintering temperature is 200~300℃ and the time is 1~60min.

9. The method for preparing a back contact battery according to claim 8, characterized in that, When the metal paste used for printing is selected from silver paste, the sintering temperature is 500~577℃ and the time is 1~30min.

10. The method for preparing a back contact battery according to claim 9, characterized in that, When the metal paste used for printing is selected from silver paste, the sintering temperature is 500~577℃ and the time is 5~30min.